2012
DOI: 10.18673/gs.v3i2.24291
|View full text |Cite
|
Sign up to set email alerts
|

A sistematização da assistência de enfermagem e as necessidades de cuidados de pacientes internados em terapia intensiva

Abstract: RESUMOEstudo exploratório descritivo, do tipo convergente assistencial. Tem como objetivo caracterizar as necessidades de cuidados de enfermagem dos pacientes internados em Unidade de Terapia Intensiva (UTI) a partir da identificação dos diagnósticos e intervenções de enfermagem mais frequentes. Os sujeitos deste estudo foram 10 pacientes internados na UTI de um hospital de ensino. A coleta de dados aconteceu mediante entrevista semi-estruturada, exame físico e observação participante.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
8

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 0 publications
0
3
0
8
Order By: Relevance
“…construction of the initial form based on literature [1,3,6,[9][10]12,14, The questionnaire consisted of questions about characteristics of nursing professionals (age, gender, and education), knowledge, attitude, and practice in oral health care. For questions about knowledge, dichotomous type responses "yes" and "no" were adopted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…construction of the initial form based on literature [1,3,6,[9][10]12,14, The questionnaire consisted of questions about characteristics of nursing professionals (age, gender, and education), knowledge, attitude, and practice in oral health care. For questions about knowledge, dichotomous type responses "yes" and "no" were adopted.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the type and consistency of food consumed during hospitalization and reduced saliva production, if oral hygiene is neglected, biofilm (plaque) and oropharynx become a reservoir suitable for the growth of microorganisms, which may be aggravated by the presence other oral diseases such as periodontal disease, dental caries, pulp necrosis, mucosal injury and trauma caused by dentures, installing remote infections, influencing the therapeutic characteristics of each patient, eventually extending the hospital stay [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Entretanto, esses estudos caracterizam-se por perfis diagnósticos de todos os domínios na NANDA-I, o que demonstra a necessidade da realização de pesquisas que focalizem o domínio segurança e proteção (14)(15)(16)(17).…”
Section: Introductionunclassified
“…This method allows the recording and communication between multidisciplinary team events linked to health status of patients who are not medical diagnoses, called Problem Oriented Medical Record (POMR). 12 According to the standard established in 1980, since when the hospital started its research activities, the care problems identified by nurses should be underlined when they are identified in the nursing record. However, this study showed that the problems are logged in a variety of ways such as: underlined in the record (such as the established norm), circulated and/or highlighted with colored pen in the nursing record, written in the evolution of nursing.…”
mentioning
confidence: 99%